Nanoemulsions of Clove Oil Stabilized with Chitosan Oleate-Antioxidant and Wound-Healing Activity - Sara Perteghella; Alice Garzoni; Alessandro Invernizzi; Milena Sorrenti; Cinzia Boselli; Antonia Icaro Cornaglia; Daniele Dondi; Simone Lazzaroni; Giorgio Marrubini; Carla Caramella; Laura Catenacci; Maria Cristina Bonferoni (MDPI AG, 2023)
Clove oil (CO) is a powerful antioxidant essential oil (EO) with anti-inflammatory, anesthetic, and anti-infective properties. It can be therefore considered a good candidate for wound-healing applications, especially for chronic or diabetic wounds or burns, where the balance of reactive oxygen species (ROS) production and detoxification is altered. However, EOs require suitable formulations to be efficiently administered in moist wound environments. Chitosan hydrophobically modified by an ionic interaction with oleic acid (chitosan oleate, CSO) was used in the present work to stabilize CO nanoemulsions (NEs). The dimensions of the NE were maintained at around 300 nm as the volume distribution for up to six months, and the CO content did not decrease to under 80% over 4 months, confirming the good stabilizing properties of CSO. The antioxidant properties of the CO NE were evaluated in vitro by a 2,2-diphenil-2-picrylhydrazyl hydrate (DPPH) assay, and in fibroblast cell lines by electron paramagnetic resonance (EPR) using α-phenyl-N-tert-butyl nitrone (PBN) as a spin trap; a protective effect was obtained comparable to that obtained with α-tocopherol treatment. In a murine burn model, the ability of CO formulations to favor macroscopic wound closure was evidenced, and a histological analysis revealed a positive effect of the CO NE on the reparation of the lesion after 18 days. Samples of wounds at 7 days were subjected to a histological analysis and parallel dosage of lipid peroxidation by means of a thiobarbituric acid-reactive substances (TBARS) assay, confirming the antioxidant and anti-inflammatory activity of the CO NE.